Active transient vibration control using a novel repetitive algorithm - Gan, Woon-Seng (2013)
In this paper, active control of periodic transient vibration based on repetitive control (RC) algorithm is studied. According to the stability condition of an active vibration control (AVC) system, a novel non-causal stable inversion approach combined with an optimal criterion is used to design the RC controller for an AVC system with a non-minimum phase secondary path. Computer simulations have been carried out to validate the effectiveness of the proposed algorithm. The plant model used in the computer simulations is obtained from a practical AVC system in our laboratory. Simulation results show that the proposed scheme can significantly reduce periodic transient vibration and the convergence rate is acceptable for a non-minimum phase plant.